2020
DOI: 10.1111/petr.13893
|View full text |Cite
|
Sign up to set email alerts
|

Augmented immunosuppression and PTCY‐based haploidentical hematopoietic stem cell transplantation for thalassemia major

Abstract: Alternate donor HSCT for thalassemia major from a matched unrelated donor or haploidentical family donor is a feasible therapeutic option in children with no matched family donor. Aggressive pretransplant immunosuppression, reduced toxicity conditioning, and PTCY result in excellent thalassemia‐free survival. We describe here our experience in this cohort. We performed a retrospective analysis of the data on children who underwent a haploidentical HSCT for thalassemia major with PTCY at our center from August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This study included a relatively large cohort of TM patients; thus, it is a representative study regarding CMV infection in TM. Accordingly, a recent study showed that 15 out of 20 (75%) CMV reactivation was found in PTCY-based haploidentical HSCT for TM ( Vellaichamy Swaminathan et al., 2021 ). Regarding matched sibling donor HSCT using in vivo T-cell depletion myeloablative conditioning, the rate of CMV reactivation was 36.2% ( Qin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study included a relatively large cohort of TM patients; thus, it is a representative study regarding CMV infection in TM. Accordingly, a recent study showed that 15 out of 20 (75%) CMV reactivation was found in PTCY-based haploidentical HSCT for TM ( Vellaichamy Swaminathan et al., 2021 ). Regarding matched sibling donor HSCT using in vivo T-cell depletion myeloablative conditioning, the rate of CMV reactivation was 36.2% ( Qin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that lower Bu levels correlated with a greater likelihood of graft rejection 29 . Moreover, even with two times pre‐transplant immune suppression therapy, a reduced intensive conditioning without Bu, including rabbit ATG, thiotepa, Flu, low doses of CTX, and 200 centi‐Grey total body irradiation (TBI), produced an unacceptably high GF rate of 20% 17 . We did not include other agents, such as treosulfan 30,31 or thiotepa, 32,33 in the conditioning regimen due to availability and medical insurance issues.…”
Section: Discussionmentioning
confidence: 99%
“…We used ATG in the conditioning regimen because it was recognized to successfully help the engraftment of allogeneic stem cells and to prevent cGVHD in patients with thalassaemia having matched or mismatched donors 7,13,39,40,44,45 . Moreover, the strategy of PTCy was adopted in recent studies of haploidentical transplantation in patients with thalassaemia 15–17,41,46 . In this study, we used a modified PTCy regimen that included two short‐term cytotoxic drugs post transplant, that is PTCy and LD‐MTX, and one long‐term calcineurin inhibitor to induce the dual immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations